ECO-BIOLOGICAL CHARACTERISTICS AND CURRENT STATE ASSESSMENT OF PHEDIMUS HYBRIDUS AND HYLOTELEPHIUM EWERSII IN THE KOK-ZHAILAU GORGE, FLORA OF THE ILE ALATAU (Experimental biology, 2024)
The article examines the current status of populations of Phedimus hybridus (L.) 't Hart (also known as Sedum hybridum L. and Aizopsis hybrida (L.) Grulich) and Hylotelephium ewersii (Ledeb.) H. Ohba (formerly Sedum ewersii Ledeb.) in the Kok-Zhailau Gorge, part of the flora of the Ile Alatau. The study explores the biology of these species, including their population dynamics and life forms, as well as their ecological responses to specific ecological-cenotic conditions. P. hybridus is valued in traditional medicine for its diverse therapeutic properties, such as anti-inflammatory effects, stimulation of the nervous system, antidepressant and wound-healing actions, and inhibition of leukocytosis. In contrast, H. ewersii is commonly cultivated as an ornamental plant. The article also includes a taxonomic, ecological, and geographical analysis of the flora associated with the populations of P. hybridus and H. ewersii in the Kok-Zhailau Gorge.
Keywords: Phedimus hybridus; Hylotelephium ewersii; coenopopulation; Kok-Zhailau Gorge; Ile Alatau